Impact of Strategic Leadership Styles and Leadership Support on Employee Engagement in Indian Higher Education - Khan, Gulzar Fatima; Bhatt, Alka Singh; Siddiqui, Masood Husain; Mishra, Manish (International Review of Management and Marketing, 2026)
This study examines the impact of strategic leadership styles and perceived supervisor support on employee engagement among faculty members in Indian higher education institutions. Given the rapid transformation of India’s higher education landscape, the research seeks to identify leadership behaviours that enhance faculty motivation, commitment, and engagement. A quantitative, cross-sectional survey design was adopted. Data were collected from 489 teaching professionals across diverse disciplines and institution types. The study analysed the influence of transformational, transactional, and laissez-faire leadership styles, alongside perceived supervisor support, on employee engagement using structural equation modelling (SEM). Results reveal that supervisor support has the strongest positive effect on employee engagement, underscoring the critical role of mentoring, recognition, and involvement. Transactional leadership, characterised by structured goal setting and reward-based motivation, also shows a significant positive impact. Transformational leadership contributes positively but to a lesser extent, while laissez-faire leadership demonstrates no significant influence on engagement. The findings are based on self-reported, cross-sectional data and are specific to Indian higher education institutions. Future studies should adopt longitudinal designs and incorporate multi-source data to validate and extend these results across different educational and cultural contexts. The study highlights the importance of supportive and structured leadership practices in fostering faculty engagement. Higher education institutions should prioritise leadership development initiatives that enhance supervisory support, effective communication, and performance-based reward systems to improve institutional outcomes. This research contributes to the limited literature on leadership and employee engagement within the Indian higher education context. By integrating leadership support alongside established leadership styles, the study offers a comprehensive framework for understanding faculty engagement and provides actionable insights for institutional policy and leadership development.